'Employ'd in Works that Womankind Become': Andromache and the Idealisation of Separate Spheres in Eighteenth‐Century Literature and Art. (15th October 2020) - Taylor, Jonathan
Abstract: Offering a counterpoint to recent demonstrations that eighteenth‐century writers subverted epic poetry's gender binaries, this article illuminates the eighteenth century's persistent invocation of Homer's Andromache as an ideal archetype of female domesticity. It explores how Homer's eighteenth‐century translators suppressed alternative representations of Andromache as a shrewd military tactician and transformed her into the archetypal domestic woman, before examining how successive eighteenth‐century writers appropriated the 'domesticated' Andromache to advocate, inculcate or police the doctrine of separate male and female (public and private) spheres. The final section explores how this trend complicates feminist interpretations of Angelica Kauffman's influential paintings of Andromache.